Análisis de la curva de capabilidad para la operación de una unidad motor generador ac-ac conectado a la barra y aislado - Estrada Lapo, Kevin Jeancarlo (2022)
This research project was analized the operation limits an AC-AC motor generator unit to have an generator optimal operation, through the chart and operation limits, what presents a synchronous generator, due to these give the conditions for operation limits, the made tests on the machine were performed into short circuit and open circuit or in vacuum to determine the generator reactances (reactance into direct axis and reactance in the quadrature axis), for the capacity curve graph execution, this graph is made on a cartesian plane, starting from a power phasor diagram, these are active and reactive, this curve is also called a thermal limit diagram, due to it determines the value, which the generator, its windings and cores reach the maximum operating temperature into a stable state, to get the graph, was used the Matlab software, what contains GUIDE into its libraries, which served to import and export data for generator operation chart execution, this was achieved to develop based onto made tests to the synchronous generator, the graph, what it presents increases the operating regime with respect to power factor, that is, the operating regime increases, when the power factor approaches the unit.